Women's struggle for the right to vote in general elections in Britain between 1897-1 - Muhammad, Dr. Adnan Amin; Department, Karwan Fatah Abdulrahman (Sulaimani Journal for Humanities, 2026)
Women in Britain have fought a long struggle for their civil rights dating back to the late eighteenth century. One of the areas in which women spent a lot of effort was the issue of obtaining the right to vote in general elections, which women were deprived of. Women's struggle for the right to vote in Britain, which is part of the history of the feminist movement, began in 1897 without political, economic and social challenges, especially the confrontation of constitutional principles that gave only men the right to vote in general elections. The study is an attempt to understand the content of the efforts and ideas of the leading women of the women's suffrage movement, in terms of presenting the steps, efforts and methods of struggle of women. The study shows that women from different sections of British society: women of the aristocracy, the middle class, the working class, worked together to secure women's suffrage in general elections. They had suffered imprisonment, hunger strikes and even sacrificed their lives for this purpose, until in 1918 they were able to achieve their rights within the framework of the constitution. Understanding the process of women's struggle for the right to vote in the UK, which was an influential factor in consolidating the principles of democracy in the country, can be seen as an important experience for promoting women's civic and organizational work in the Kurdistan Region and elsewhere.
Keywords: Women; suffrage; struggle; Britain; society